Primary aortic intimal sarcoma masquerading as intramural hematoma - Fan Xiaodong (De Gruyter, 2021)
Primary aortic intimal sarcoma is a very rare disease and most patients present with features similar to those of atherosclerotic plaque and thrombus; however, primary aortic intimal sarcoma presents with features similar to those of intramural hematoma (IMH) on CT imaging and clinical presentation had never been previously reported. Here we report a case involving a 49-year-old woman with primary aortic intimal sarcoma masquerading as IMH on radiological images and clinical presentation. We also discuss some of the diagnostic pitfalls and hope that these diagnostic pitfalls will be very useful for clinicians.